Recurring Decorative Patterns Between Sensory Organization and Attentional Distraction in Individuals on the Autism Spectrum: An Analytical Psychological Study (Comprehensive Journal of Science, 2026)
AbstractThe study aimed to explore the psychological dimensions of this attraction and to develop strategies for structuring the physical environment and employing patterns as motivational and therapeutic tools.The research adopted a descriptive-analytical approach, utilizing literature review methods and analyzing environmental structuring protocols alongside behavioral interventions. The findings revealed that decorative patterns function as neural organizers for the autistic brain amid perceptual chaos. Additionally, strategies such as visual neutrality and minimalist classroom design were shown to significantly reduce excessive cognitive load and increase both sitting duration and attention span. The results also demonstrated the effectiveness of interactive technology and virtual reality in achieving sensory calibration and enhancing joint attention skills through gradual fading techniques.The study recommended re-engineering educational spaces to include organized sensory corners, training educational staff to integrate decorative art (such as mandalas) as a functional sensory-regulation tool, and emphasizing the role of the family in regulating the home sensory rhythm to sustain therapeutic outcomes. Furthermore, it suggested the need to investigate the impact of augmented reality technologies on improving attentional shifting flexibility among individuals with autism.